Implementing energy efficient cooperative diversity antenna arrays in wireless sensor network - Zhao, Danlin. (2013)
Cooperative diversity has been recently proposed as a way to form virtual antenna arrays to combat slow fading and save energy. However, compared with mobile telecommunication networks, which is mostly focused on by many researchers, the wireless sensor network (WSN) is more suitable for implementing cooperative technology, simply because the sensor nodes are neither selfish, nor complicated, and they are more energy efficient.